Energetic exploitation from a hybrid PV-wind power micro-generation rural electrification - Seraphim, Odivaldo José [UNESP]; Siqueira, Jair Antonio Cruz; Putti, Fernando Ferrari [UNESP]; Gabriel Filho, Luís Roberto Almeida [UNESP]; Cremasco, Camila Pires; Daltin, Rodrigo Serra [UNESP] (Elsevier B.V., 2014)
Hybrid system micro-generation integration of PV-wind power is presented by a form of energy in which problems resulting from variability in the intensity of wind and solar intensity are possible mitigation either by complementation between one source to another or the largest stability configured by the generate the system. Based on this context, this work aims to assessing the performance of a hybrid system PV-wind power energy small of a rural property for their electrification. The study has been developed at the Rural Laboratory Powering from Engineering Department of UNESP. In order to present this research, a hybrid system has been installed PV-wind power, composed of one 400Wp windmill and a 300 Wp PV-system. The results obtained allowed us to evaluate the solar and wind energy supplied ranked among 285 and 360 kWh electric power generated by the PV-wind power hybrid system stood between 25,5 and 31 kWh. At is to say achieving yield of approximately than 10% during one year observation period, i.e., it was concluded that the performance of the hybrid system depended essentially the energy received and generated by the PV-system and that there was complementation between generating wind power and PV-systems with regard to time of day and the annual seasons by confirming the technical feasibility of this kind system of micro-generation in small rural properties.
Keywords: Aeolic energy; Photovoltaic solar system; Rural electrification